Epoxide Ring-Opening Reactions of Two Diastereomeric 1,2- Epoxy-3-(N-benzyl-N-methylamino)cycloheptanes - A. Larin, Evgeni; S. Kochubei, Valeri; M. Atroshchenko, Yuri (Letters in Organic Chemistry, 2016)
Background: Cyclic amino alcohols comprise one of the most important functional motifs of aminoglycoside-type antibiotics. Development of the strategies towards new cyclic amino alcohols allows a broader investigation of these compounds in biology and medicine. Much attention is paid to the preparation of aminoglycoside mimetics that have simpler structures, but retain the biological activity of parent structures. Oxirane ring opening is a synthetically significant reaction for the creation of new pharmaceutically important scaffolds. A distinguishing feature of this approach is the synthesis of amino alcohols with the assigned stereochemistry. Regio- and stereochemical diversity within a sugar-like moiety in those mimetics may subtly influence their biological activity. We propose a regio- and stereospecific route towards trisubstituted cycloheptanes. Methods: Initially, two diastereomeric 1,2-epoxy-3-(N-benzyl-N-methylamino)cycloheptanes with opposite orientation of the oxirane ring to the amino moiety were synthesized. Then, epoxide ring-opening reactions with different nucleophiles under acid- or base-catalyzed conditions were performed. The structure of the products was confirmed by two dimentional NMR methods. Results: Three types of regioisomers, according to the direction of the nucleophilic attack, were obtained. The regio- and stereoselective outcome of these reactions depends on the relative orientation of the oxirane ring and the nature of the catalyst. Conclusion: In summary, the regio- and stereospecific outcome of the epoxide ring cleavage of 1,2-epoxy-3- substituted cycloheptanes was highlighted. The route allows to synthesize new regio- and stereochemically diverse aminocycloheptanol derivatives on multi-gram scale, which could serve as prospective building blocks for the aminoglycoside antibiotic research. The benzyl removal and the further functionalization of nitrogen atom could provide the creation of novel scaffolds for the pharmaceutical and biotech research communities.
Keywords: aminocycloheptanol